Bottom-up synthesis of functionalized {Ce4(SiW9O34)2(l)2} polyoxometalates. Issue 44 (24th October 2018) - Dufaye, Maxime; Duval, Sylvain; Nursiah, Kelvinraj; Stoclet, Gregory; Trivelli, Xavier; Loiseau, Thierry
Abstract : Bottom-up synthesis allows the formation of four organic-functionalized Ce IV containing polyoxometalates and one unprecedented polyanion stabilizing two different Ce IV clusters. Abstract : The reaction of Na10 [SiW9 O34 ] with the 4f tetravalent cerium cation associated with four different organic O/N-donor ligands at pH = 4–4.5 gives rise to the formation of five anionic polyoxometalates [Ce4 (μ 3 -O)2 (SiW9 O34 )2 (C4 H5 O4 )2 ] 10− (1 ), [Ce4 (μ 3 -O)2 (SiW9 O34 )2 (C5 H7 O4 )2 ] 10− (2 ), [Ce4 (μ 3 -O)2 (SiW9 O34 )2 (C5 H8 O2 –NH3 )2 ] 8− (3 ), [Ce4 (μ 3 -O)2 (SiW9 O34 )2 (C6 H10 O2 –NH3 )2 ] 8− (4 ) and [(Ce3 (μ 3 -O)(μ 2 -OH)3 )(Ce6 (μ 3 -O)4 (μ 3 -OH)4 )(SiW9 O34 )4 ] 21− (5 ). Compounds1–4 consist of one tetranuclear Ce-based cluster fragment stabilized by two [SiW9 O34 ] 10− polyanions and two organic linkers. Compound5 is composed of a hexanuclear core combined with a trinuclear cerium core, stabilized by four [SiW9 O34 ] 10− moieties. The molecular species were characterized by single-crystal and powder X-ray diffraction, IR spectroscopy, TGA, SEM/EDX, SAXS and ICP analysis. The solution stability of compounds1–4 was also assessed by 29 Si and 183 W NMR.